Physicochemical characterization of the Tunants and Yahuahua lakes for conservation purposes, Amazonas region, Peru - Morales Rojas, Eli (2022)
The objective of this research was to characterize the water in the lakes of the native communities, Tunants and Yahuahua, for the purpose of conservation of the aquatic environment. Two sampling points were established, one for each lake, and the evaluations were carried out during the months of December, January and February 2020. Physicochemical parameters of pH, Ce, TSS, Nitrates, BOD5 were analyzed. The results show a pH of 7 for both lakes. Regarding BOD5, in Tunants lake the median was found to be 1.8 mg/L of O2 and in Yahuahua lake the median was found to be between 1.45 mg/L of O2. The physicochemical parameters were found to be within water quality standards of Supreme Decree N° 004-2017-MINAM. Category 4: Conservation of the aquatic environment. However, the only parameter that did not meet the standard was Total Suspended Solids (TSS). Finally, the physicochemical characterization allows to know the current state of the lakes for future decisions in order to conserve the aquatic environment for its potential ecotourism use.